1996
DOI: 10.1002/pssb.2221970134
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ionicity and nonlinear refractive index in alkali halides

Abstract: A relationship between the generalized Miller 61111(w; w , w , w ) coefficient and the Phillips-van Vechten ionicity in alkali halides is presented. The correlation is employed to estimate the nonlinear refractive index of these crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…In such dielectrics the relationship between n 2 and the crystal ionicity could be different from that given by equations ( 7) and ( 8). This is in agreement with results presented by Górski et al (1996) for alkali halides, for which a stronger increase in δ(ω; ω, ω, ω) with f i than that predicted by equation ( 8) was found. The numerical values of Adair et al (1989) are based, however, on the lowest scale adopted in the literature.…”
Section: Miller's Third-order δ Ijkl (ω; ω ω ω)supporting
confidence: 93%
See 1 more Smart Citation
“…In such dielectrics the relationship between n 2 and the crystal ionicity could be different from that given by equations ( 7) and ( 8). This is in agreement with results presented by Górski et al (1996) for alkali halides, for which a stronger increase in δ(ω; ω, ω, ω) with f i than that predicted by equation ( 8) was found. The numerical values of Adair et al (1989) are based, however, on the lowest scale adopted in the literature.…”
Section: Miller's Third-order δ Ijkl (ω; ω ω ω)supporting
confidence: 93%
“…This recommended scale, which is roughly midway between the lowest (Adair et al 1989) and the highest (Smith et al 1975) proposed scales, is also in good agreement with two other sets of absolute values derived from calibrations based on Raman scattering cross sections (Marker and Terhune 1965, Levenson 1974, Lynch et al 1974. According to the previous findings (Kucharczyk 1995, Górski et al 1996, the numerical values reported by Adair et al (1989) should be multiplied by a factor of about 2.3 to be in agreement with the scales used by Levenson and Bloembergen (1974), Levenson (1974), Lynch et al (1974 and Landolt-Börnstein New Series (1984).…”
Section: Miller's Third-order δ Ijkl (ω; ω ω ω)supporting
confidence: 87%